2011
DOI: 10.1042/cs20100427
|View full text |Cite
|
Sign up to set email alerts
|

Blood levels of glutamate oxaloacetate transaminase are more strongly associated with good outcome in acute ischaemic stroke than glutamate pyruvate transaminase levels

Abstract: Ischaemic stroke is associated with an excessive release of glutamate in brain. GOT (glutamate-oxaloacetate transaminase) and GPT (glutamate-pyruvate transaminase) are two enzymes that are able to metabolize blood glutamate facilitating the lowering of extracellular levels of brain glutamate. Our aim was to study the association between blood levels of both enzymes and stroke outcome in patients with acute ischaemic stroke. We prospectively studied 365 patients with first ischaemic stroke<12 h. Glutamate, GOT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 23 publications
7
73
3
Order By: Relevance
“…Campos et al further showed that lower blood glutamate levels and higher levels of GOT were associated with better neurological outcome in patients after ischemic stroke [41][42][43]. Considering the close relationship between low blood and CSF glutamate levels, the results of the current study suggest that oxaloacetate and pyruvate provide their neuroprotective properties via a glutamate-scavenging mechanism.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Campos et al further showed that lower blood glutamate levels and higher levels of GOT were associated with better neurological outcome in patients after ischemic stroke [41][42][43]. Considering the close relationship between low blood and CSF glutamate levels, the results of the current study suggest that oxaloacetate and pyruvate provide their neuroprotective properties via a glutamate-scavenging mechanism.…”
Section: Discussionmentioning
confidence: 59%
“…The efflux of glutamate into the blood resulted in increased concentrations of radiolabeled glutamate in the blood and its disappearance from the CSF [34]. Magnetic resonance spectroscopy confirmed that blood glutamate scavengers oxaloacetate and GOT are capable of decreasing ECF glutamate concentrations via blood glutamate elimination in a rat model of experimental focal ischemia [41][42][43].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…57,58 Similar to previous studies with GOT, GPT levels were associated with lower levels of blood glutamate, better functional outcome, reduced infarct volume, and lower percentages of early neurological deterioration, although this association was stronger for GOT than GPT levels. 50 Similarly, in experimental studies, OxAc presented stronger protective effects than pyruvate. 57,58 Hemodialysis and peritoneal dialysis Another interesting and potentially useful method for reducing blood glutamate concentrations is the use of dialysis to filter the blood and remove excess glutamate.…”
Section: Other Blood Glutamate Lowering Strategies Pyruvatementioning
confidence: 99%
“…To test this hypothesis, two independent clinical and observational studies were performed, in which the primary end point was functional outcome at three months. 50,51 In these studies, patients with good outcomes showed lower glutamate levels and higher GOT levels in blood samples collected at admission. A significant inverse correlation was observed between GOT and glutamate levels.…”
Section: Previous Strategies To Reduce the Glutamate Excitotoxicitymentioning
confidence: 99%